A Role for Epigenetic Regulation in the Adaptation and Stress Responses of Non-model Plants - Thiebaut, Flávia; Hemerly, Adriana Silva; Ferreira, Paulo Cavalcanti Gomes (Frontiers in Plant Science, 2019)
In recent years enormous progress has been made in understanding the role of epigenetic regulation response to environmental stimuli, especially in response to stresses. Molecular mechanisms involved in chromatin dynamics and silencing have been explained, leading to an appreciation of how new phenotypes can be generated quickly in response to environmental modifications. In some cases, it has also been shown that epigenetic modifications can be stably transmitted to the next generations. Despite this, the vast majority of studies have been carried out with model plants, particularly with Arabidopsis, and very little is known on how native plants in their natural habitat react to changes in their environment. Climate change has been affecting, sometimes drastically, the conditions of numerous ecosystems around the world, forcing populations of native species to adapt quickly. Although part of the adaptation can be explained by the preexisting genetic variation in the populations, recent studies have shown that new stable phenotypes can be generated through epigenetic modifications in few generations, contributing to the stability and survival of the plants in their natural habitat. Here, we review the recent data that suggest that epigenetic variation can help natural populations to cope to with change in their environments.